Regulating Digital Health: Legal Perspectives on Medical ICT and Home Wellness Devices - Mahmud, Kafi; Kumar, Mukesh; Midha, O.P. (Journal of Cultural Analysis and Social Change, 2025)
Medical Information and Communication Technologies (ICT) and Home Wellness devices that have proliferated are transforming healthcare delivery offering remote monitoring and personalized care. Yet such advancement also brings important regulatory challenges such as fragmented legal frameworks, privacy of data, device safety and liability issues. In this paper, the current legal regulation of Medical ICT and home wellness devices is studied and, with a focus on their regulatory gaps and difficulties in effective oversight, is researched. The first research questions address how these technologies are regulated by existing international and domestic legal frameworks and what legal issues are created when innovations are pitted against patient protection. Using a qualitative doctrinal methodology, the study carries out a systematic analysis of relevant statutes, regulations and judicial decisions to build a legal view of the issue. Scope includes medical devices subject to regulation by health authorities as well as wellness devices imagined at the crossroads of consumer technology and healthcare. Results illustrate regulatory approaches keeping up with the changes and inconsistences in regulatory approach, jurisdictional ambiguities and the necessity of further harmonization when dealing with new technological underpinnings. Finally, the study presents targeted legal reforms and an ongoing regulatory strategy, aimed at assuring patient safety, data security and accountability, while promoting innovation. The academic and practical discourse on digital health regulation is expanded by this research through a rigorous legal analysis that is critical for policymakers, regulators and stakeholders involved in the increasingly dynamic context of medical ICT and home wellness device governance.